The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/clockssleep2040030
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in Patients with Persistent Delusions: Prevalence, Clinical Associations, and Therapeutic Strategies

Abstract: Sleep disturbances accompany almost all mental illnesses, either because sound sleep and mental well-being share similar requisites, or because mental problems lead to sleep problems, or vice versa. The aim of this narrative review was to examine sleep in patients with delusions, particularly in those diagnosed with delusional disorder. We did this in sequence, first for psychiatric illness in general, then for psychotic illnesses where delusions are prevalent symptoms, and then for delusional disorder. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 103 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Sleep disorders have been frequently reported in patients with psychosis, including DD [ 79 , 80 ]. Distressing delusional beliefs often haunt patients at night, either preventing sleep or populating nightmares.…”
Section: Collaboration With Sleep Specialistsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep disorders have been frequently reported in patients with psychosis, including DD [ 79 , 80 ]. Distressing delusional beliefs often haunt patients at night, either preventing sleep or populating nightmares.…”
Section: Collaboration With Sleep Specialistsmentioning
confidence: 99%
“…Insomnia is the most frequent sleep disorder found in patients with DD [ 79 ], and it is associated with an aggravation of paranoid and cognitive symptoms, as well as suicidal ideation. Insomnia and other sleep problems are difficult to address and often require the expertise of sleep specialists.…”
Section: Collaboration With Sleep Specialistsmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 6 Studies have shown that sleep disturbance is a potential risk factor for major health problems. 7 8 Sleep disturbances may be related to several mental and cognitive disorders including persistent delusions, 9 depression, anxiety and dementia 10 and often coexist with major medical conditions, such as hypertension, 11 12 diabetes 13 and cancer, 14 which may increase pain and even increase the risk of mortality. 15 16 Therefore, sleep disturbance is an important therapeutic target for healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…A great volume of literature has robustly supported the co-occurrence of insomnia and psychosis, including in clinical populations, those at ultra-high-risk for psychosis, and the general population. [1][2][3][4] While research in clinical populations (patients with schizophrenia or other psychotic disorders) aims to explore the interaction between insomnia and psychosis in predicting clinical symptomatology, functions and treatment, 5,6 studies in non-clinical populations are essential to understanding their potential relationship in the absence of antipsychotic medication and institutionalisation effects, 7 which also provides information on prevention at an early stage.…”
Section: Introductionmentioning
confidence: 99%